Analysis on Reported Cases of HIV at Ekiti State University Teaching Hospital, Ado-Ekiti, South-Western Nigeria - Ajao, Isaac O.; Ibikunle, Kayode S. O. (Transactions on Engineering and Computing Sciences, 2019)
The nation Nigeria has been ranked the second among the nations of world with largest population of people with HIV. This information does not mean that every region and state in the country is not safe. Ekiti, a state in the south western part of the country has the lowest rate, which this study aims at establishing scientifically. Considering certain risk factors, such as age, gender and the local government area of the individuals tested, it is found out that none of the factors is significantly contributing to having or not having HIV in the state at 5% of significance. The parameter estimates obtained using the binary logistic regression are very low, the lack of fit test and the model test show that the factors are not good for modelling HIV cases in Ekiti state, thereby corroborating the fact that the state has lowest rate in Nigeria.